EMPREENDEDORISMO: UMA ANÁLISE EM PRESIDENTE EPITÁCIO - Aline de Morais Cristo Melo; Paulo Roberto Rosa (Universidade do Oeste Paulista, 2014)
Nowadays entrepreneurship is studied increasingly by institutions of higher education, various articles and entities with a view to show the profile and characteristics of the entrepreneur. Being critical to the success of the company. There are differences between entrepreneurs and businessmen, businessman merely administer conservative style, since the entrepreneur creates a business and are looking to renew itself. Being an entrepreneur is not easy, there are many characteristics that identify an entrepreneur, including, initiative, seeks opportunities, persuasion, use of influence and leadership strategy. The importance of preparing the business plan for company presentation or a new business. Therefore, it was investigated along with an entrepreneurial city Presidente Epitácio, which reported their daily how to be enterprising tourist, focused this point for him to open a new business in the municipality. Thus, it is expected to contribute to the focus of tourism in the city of Presidente Epitácio and region.